Toxic Productivity dengan Burnout Pada Mahasiswa Pekerja - Nur Hamidah; Nindia Pratitis; Andik Matulessy (JIWA: Jurnal Psikologi Indonesia, 2026)
This study aims to empirically examine the relationship between toxic productivity and burnout among students who maintain a dual role as workers in Surabaya. The problem focuses on the phenomenon of excessive productivity drive in a metropolitan city, which often forces students to ignore their self-capacity limits, thereby triggering chronic emotional exhaustion. This research employs a quantitative approach with a correlational design. The participant selection technique used was purposive sampling, involving 144 active students working full-time, part-time, or freelance in the Surabaya area. The research instruments consisted of the Toxic Productivity Scale, developed based on Ramadhina’s (2021) aspects, and the Burnout Scale, referring to Maslach and Leiter’s (2016) aspects. The results of the Pearson Product Moment correlation analysis showed a correlation value of r=0.405 with a significance of p=0.000 (p<0.05), indicating a significant positive relationship between toxic productivity and burnout. The effective contribution of toxic productivity to burnout was 16.4%. This implies that the higher the level of toxic productivity in working students, the higher the level of burnout they experience. Keywords: burnout; early adulthood; mental health; toxic productivity; working students Permasalahan dalam penelitian ini berfokus pada fenomena dorongan toxic productivity di kota metropolitan yang sering kali memaksa mahasiswa mengabaikan batas kemampuan diri sehingga memicu burnout yang kronis. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Teknik pengambilan partisipan yang digunakan adalah purposive sampling dengan jumlah partisipan sebanyak 144 mahasiswa aktif yang bekerja (purna waktu, paruh waktu, maupun freelance) di wilayah Surabaya. Instrumen penelitian terdiri atas Skala Toxic Productivity yang disusun berdasarkan aspek dari Ramadhina (2021) serta Skala Burnout yang mengacu pada aspek dari Maslach dan Leiter (2016). Hasil uji korelasi Product Moment dari Pearson menunjukkan nilai korelasi sebesar r=0,405 dengan signifikansi p=0,000 (p<0,05), yang menunjukkan adanya hubungan positif yang signifikan antara toxic productivity dan burnout. Sumbangan efektif yang diberikan toxic productivity terhadap burnout sebesar 16,4%. Artinya, semakin tinggi dorongan toxic productivity pada mahasiswa pekerja, maka semakin tinggi pula tingkat burnout yang mereka alami. Kata kunci: burnout; dewasa awal; kesehatan mental; mahasiswa pekerja; toxic productivity.